Fashion trends a consumptive lifestyle in a student environment: Case study of student of the Faculty of Economics, Bengkulu University - Lupita Sari (Jurnal Sosiologi Dialektika, 2022)
This study analyzes consumptive behaviour following fashion trends as a lifestyle carried out students of the Faculty of Economics, Bengkulu University. Students tend to shop according to current fashion trends rather than buying as needed. The purpose of the study was to see consumptive behaviour following fashion trends carried out by students of the Faculty of Economics, University of Bengkulu. The theoretical basis of Jean Baudrillard is used to analyze a consumptive society that is no longer bound by morality and adopted habits. The method used is a qualitative method with case studies. In previous studies, the study of consumptive lifestyles was more focused on their consumptive lifestyle and behaviour. However, this study tries to explain the consumptive lifestyle through Baudrillard’s analysis of consumerism which is influenced by social relations and external factors. The results of this study are female students who behave consumptively based on the modern lifestyle. Students no longer buy goods based on the function of the goods themselves. However, it has become part of a habit that serves to demonstrate the ability to own trendy items. As for the factors behind students becoming consumptive of fashion trends, there are two, namely internal factors and external factors.